Determinants of Technical Efficiency in Rice Production: Evidence from Chitwan, Nepal - Shrestha, Suman; Dhungana, Surya Mani; Chaudhary, Raj Narayan (Journal of Agriculture and Forestry University, 2026)
This study aims to investigate the level of technical inefficiency as well as determine the attributes related to farmers that significantly influence the inefficiency in rice production. Multistage sampling procedure was employed to select the respondents from the primary rice cultivating areas. The data were collected through face-to-face interview with randomly selected 150 respondents from sampling frame through deployment of semi-structured questionnaire. One step stochastic frontier modelling was employed to measure the technical inefficiency, which also simultaneously estimate the inefficiency model. The estimation of the parameters in production function revealed that 1% increase in area, human labor and working capital, increases output by 0.037, 0.189, and 0.421, % respectively. The return to scale was calculated 0.647, implying diminishing return. The average technical efficiency was 82.30%, indicating, on average, farmers could increase the output by 17.70%, with the existing technologies by following best practices. The results from the inefficiency model showed that major source of household income, education, experience, cooperative membership and extension services negatively and significantly influence the inefficiency. The empirical evidences provide guidance to policy makers to target the key determinants that improve efficiency, ultimately enhancing production and productivity.